1992
DOI: 10.1177/109114219202000202
|View full text |Cite
|
Sign up to set email alerts
|

Withholding Position and Income Tax Compliance: Some Experimental Evidence

Abstract: There is a common belief that tax withholding systems have worked not only as Abstract efficient tax collection mechanisms but also as effective tax evasion controls.However, little is known about the role of withholding in tax compliance beyond the fact that withholding may reduce opportunities for evasion. This article analyzes in an experimental setting some effects that withholding may have on tax compliance. In particular, three hypotheses are examined concerning the reasons that individuals who unexpecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 11 publications
2
15
0
Order By: Relevance
“…For example, some research finds that individuals in a "balance-due position" (loss context) have a tendency to adopt more aggressive reporting behavior and report less income than taxpayers in a "refund position" (gain context) (e.g., Dusenbury [1994], Christian and Gupta [1994], Chang, Nichols, and Schultz [1987], Schepanski and Kelsey [1990], White, Harrison, and Harrell [1993]). However, several other studies do not find that the frame influences reporting behavior (e.g., Hite, Jackson, and Spicer [1988], Schadewald [1989], Martinez-Vazquez, Harwood, and Larkins [1992]). In addition, even studies supporting decision-context effects indicate that individuals tend to be overall risk averse in their tax-filing choices (e.g., Dusenbury [1994], Christensen and Hite [1997], Collins, Milliron, and Toy [1990]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, some research finds that individuals in a "balance-due position" (loss context) have a tendency to adopt more aggressive reporting behavior and report less income than taxpayers in a "refund position" (gain context) (e.g., Dusenbury [1994], Christian and Gupta [1994], Chang, Nichols, and Schultz [1987], Schepanski and Kelsey [1990], White, Harrison, and Harrell [1993]). However, several other studies do not find that the frame influences reporting behavior (e.g., Hite, Jackson, and Spicer [1988], Schadewald [1989], Martinez-Vazquez, Harwood, and Larkins [1992]). In addition, even studies supporting decision-context effects indicate that individuals tend to be overall risk averse in their tax-filing choices (e.g., Dusenbury [1994], Christensen and Hite [1997], Collins, Milliron, and Toy [1990]).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a consideration of affect in risky decision making can advance both accounting and psychological theories of risky decision making. In addition, the consideration of affect may explain the anomalous results that are sometimes found when investigating accounting decision making in gain/loss contexts (e.g., Dusenbury [1994], Martinez-Vazquez, Harwood, and Larkins [1992]).…”
Section: Introductionmentioning
confidence: 99%
“…Alm et al (1993b) find that subjects pay more in taxes when they choose, via voting, the use of their taxes than when the identical use is imposed upon them, that compliance is somewhat greater when the vote is decisive (and made public) than when the vote is close (and kept secret), and that compliance is significantly and dramatically lowered by the imposition of an unpopular program. Surprisingly, Martinez-Vazquez et al (1992) find that compliance does not seem to be significantly affected by withholding systems, at least beyond the obvious channel that withholding reduces the opportunities for evasion. Subjects who find themselves unexpectedly underwithheld do not behave much differently than subjects who are correctly antici-pate the underwithholding, and there is little difference in compliance between taxpayers who are under-or overwithheld.…”
Section: Fiscal Institutionsmentioning
confidence: 66%
“…-Vazquez, Harwood, and Larkins (1992) observed that people with liquidity problems were less likely to pay commercial debts and theorized that liquidity problems may have the same effect on the behavior of taxpayers. In two sets of experiments they found that if the possibility of evading taxes in a safe manner existed, a near-majority of people would take that chance, and the proportion of individuals choosing to evade who were in an illiquid position was significantly larger.…”
Section: Differences Between the Income Tax And The Retail Sales Taxmentioning
confidence: 99%
“…Perhaps one of the most important findings in this study is that trust is misplaced in the tax environment. Remember that Martinez-Vazquez, Harwood, and Larkins (1992) found in their experiments that given the safe opportunity to evade taxes, a near-majority of people would take that chance and, if in an illiquid position, a significantly larger proportion of people would choose to evade. The findings in this study support this premise.…”
Section: Explaining Sales Tax Theft Through the Theory Of Planned Behmentioning
confidence: 99%